Close your eyes to see, hold your breath to breathe. - Siti Salleha Rashid. (2009)
To delve into a subject matter like suicide is complex, encumbered with different contexts and different viewpoints. There are many complications in dealing with the issue of photographing suicide, sensitivity and subjectivity being two main concerns underlying this project. In the hope of not being didactic, there is a sense of ambiguity within the images, which leaves the eventual photographs or documentations open to interpretations, but with avoidance on nonchalance to the images as being merely aesthetic and too objective. This project, in a sense, is more of a personal edification than it is a public sermon on awareness.